Developing an instruments to measure prospective teacher beliefs about mathematical problem-solving using the Rasch model - Muhtarom, Muhtarom (Universitas Hamzanwadi, 2024)
Beliefs in solving mathematical problems become the basis for action, the basis for change, and the basis for learning mathematics. This research describes the development of an instrument for measuring prospective teachers beliefs in solving mathematical problems. One hundred sixty prospective teachers’ with experience in problem-solving and learning mathematics became research respondents. The research data was analysed using the Rasch model. The results of the data analysis show that the instrument developed is considered reliable and valid. Fifty-five items can be used to measure prospective teachers’ beliefs about solving mathematical problems. The instruments that have been developed can be used as initial assessments in implementing problem-based learning to help students develop problem-solving skills to face challenges in real life.